Complex‐Shaped Cellulose Composites Made by Wet Densification of 3D Printed Scaffolds. (9th December 2019) - Hausmann, Michael K.; Siqueira, Gilberto; Libanori, Rafael; Kokkinis, Dimitri; Neels, Antonia; Zimmermann, Tanja; Studart, André R.
Abstract: Cellulose is an attractive material resource for the fabrication of sustainable functional products, but its processing into structures with complex architecture and high cellulose content remains challenging. Such limitation has prevented cellulose‐based synthetic materials from reaching the level of structural control and mechanical properties observed in their biological counterparts, such as wood and plant tissues. To address this issue, a simple approach is reported to manufacture complex‐shaped cellulose‐based composites, in which the shaping capabilities of 3D printing technologies are combined with a wet densification process that increases the concentration of cellulose in the final printed material. Densification is achieved by exchanging the liquid of the wet printed material with a poor solvent mixture that induces attractive interactions between cellulose particles. The effect of the solvent mixture on the final cellulose concentration is rationalized using solubility parameters that quantify the attractive interparticle interactions. Using X‐ray diffraction analysis and mechanical tests, 3D printed composites obtained through this process are shown to exhibit highly aligned microstructures and mechanical properties significantly higher than those obtained by earlier additively manufactured cellulose‐based materials. These features enable the fabrication of cellulose‐rich synthetic structures that more closely resemble the exquisite designs found in biological materials grown by plants in nature. Abstract : 3D printing of aqueous‐based cellulose inks followed by wet densification and monomer infiltration processes offers a versatile approach for the digital manufacturing of complex‐shaped composites with high concentrations of a sustainable material resource. Wet densification is induced by a solvent exchange process that modifies the cohesive energy of the liquid medium to promote attractive interactions between the cellulose particles.